Dari Gagasan ke Lapangan: Menelusuri Implementasi Kurikulum Lokal dalam Perwako Padang no 7 tahun 2024 - Diva Octavia Armanda (CV. ITTC INDONESIA, 2025)
Local curriculum policy is an educational strategy aimed at strengthening cultural identity and local wisdom through the school system. In Padang City, this effort is realized through Mayor Regulation Number 7 of 2024, which regulates the implementation of local content at educational institutions, including scheduling and mapping of student memorization tasks. This article aims to trace the formulation and implementation process of the policy, based on direct observation at the Padang City Regional House of Representatives (DPRD). The study employs a qualitative approach using observation and in-depth interviews with relevant stakeholders. The findings reveal that the legislative process is strongly influenced by community participation, political support, and inter-sectoral coordination. Major challenges in implementation include the lack of teacher training and limited availability of teaching materials. Strategic efforts are needed to improve policy outcomes, particularly by enhancing human resource capacity and establishing a structured and continuous evaluation mechanism.